2021
DOI: 10.18371/fcaptp.v1i36.227924
|View full text |Cite
|
Sign up to set email alerts
|

Formation of an Effective Risk Management System at the Enterprise

Abstract: The purpose of the article is developing a risk management system in the aviation industry. After analyzing the works of many scientists, such concepts as «risk», «risk management» were considered and their importance in business was highlighted. This article provides a coefficient analysis of the financial condition of one of the largest airlines in Ukraine PJSC «International Airlines of Ukraine». The authors pay special attention to external and internal factors, which are the main result of losses fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…SC financing business is different from traditional bank financing products in that it selects well-qualified SMEs as credit targets based on the credit guarantee of core enterprises in the SC [17]. Given the unique attributes of SC financing business, the sample enterprises should be selected from SMEs in the same industry with obvious SC patterns.…”
Section: Data Collection and Allocationmentioning
confidence: 99%
“…SC financing business is different from traditional bank financing products in that it selects well-qualified SMEs as credit targets based on the credit guarantee of core enterprises in the SC [17]. Given the unique attributes of SC financing business, the sample enterprises should be selected from SMEs in the same industry with obvious SC patterns.…”
Section: Data Collection and Allocationmentioning
confidence: 99%
“…Tereshchenko et al argue that, however, judging from the current situation of Chinese enterprise practice and theoretical research, to effectively evaluate and control corporate financial risks in China, there are still big gaps. Under the planned economic system, the financial risks of Chinese enterprises are borne by the state; however, with development of socialist market economy and establishment of modern enterprise system with the further integration of China and the western enterprise system after China's entry into the WTO, enterprises should constantly establish financial risk awareness and possess the ability to undertake and resolve corporate financial risks [ 8 ]. Hemmer and Moore found that the external environment in which enterprises are located is complex and changeable, and this complex and changeable external environment will bring risks to enterprises [ 9 ].…”
Section: Literature Reviewmentioning
confidence: 99%